(untitled) (Baltic Journal of Sport and Health Sciences, 2025)
This study evaluates the validity and reliability of the Hebrew version of the Children’s Attitudes Toward Inclusion in Physical Education – Israel, Multi-Scenario (CAIPE-IL-MS) questionnaire, aimed at assessing attitudes towards including children with disabilities in physical education (PE) classes. A sample of 258 students aged 11 to 15 from five schools participated, responding to four case studies involving children with various disabilities through 13 questions rated on a 4-point scale. One questionnaire was removed due to inconsistent structure. Data analysis utilized exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), dividing responses into two subsamples (n=83 for EFA, n=175 for CFA). EFA revealed a two-factor model, each with three items addressing (1) general attitudes toward inclusion and (2) willingness to modify game rules for children with disabilities. CFA confirmed the model’s fit with strong indices (CFI=0.963, SRMR=0.042, RMSEA=0.036). Internal reliability was assessed, yielding Cronbach’s alpha values of 0.825 for Factor 1 and 0.657 for Factor 2, with an overall scale reliability of 0.792. These results indicate that this questionnaire is a valid and reliable instrument for measuring attitudes towards inclusion in PE environments. Keywords: Integration, disabilities, school, adaptation